Ethnographic Study : Understanding The Usage Of English Language At KUIM - Hazleena Baharun; Tun Nur Afizah; Rozlina Mohd Ramli; Queshaira Zainudin; Abd. Aziz Mohd; Suhaili Abd. Jalil (Universiti Sains Islam Malaysia, 2024)
Research project (UPU (1)/F/2001)-Kolej Universiti Islam Malaysia, 2001.